Seasonal Expression of Avian and Mammalian Daily Torpor and Hibernation: Not a Simple Summer-Winter Affair† - Geiser, Fritz (Frontiers in Physiology, 2020)
Daily torpor and hibernation (multiday torpor) are the most efficient means for energy conservation in endothermic birds and mammals and are used by many small species to deal with a number of challenges. These include seasonal adverse environmental conditions and low food/water availability, periods of high energetic demands, but also reduced foraging options because of high predation pressure. Because such challenges differ among regions, habitats and food consumed by animals, the seasonal expression of torpor also varies, but the seasonality of torpor is often not as clear-cut as is commonly assumed and differs between hibernators and daily heterotherms expressing daily torpor exclusively. Hibernation is found in mammals from all three subclasses from the arctic to the tropics, but is known for only one bird. Several hibernators can hibernate for an entire year or express torpor throughout the year (8% of species) and more hibernate from late summer to spring (14%). The most typical hibernation season is the cold season from fall to spring (48%), whereas hibernation is rarely restricted to winter (6%). In hibernators, torpor expression changes significantly with season, with strong seasonality mainly found in the sciurid and cricetid rodents, but seasonality is less pronounced in the marsupials, bats and dormice. Daily torpor is diverse in both mammals and birds, typically is not as seasonal as hibernation and torpor expression does not change significantly with season. Torpor in spring/summer has several selective advantages including: energy and water conservation, facilitation of reproduction or growth during development with limited resources, or minimisation of foraging and thus exposure to predators. When torpor is expressed in spring/summer it is usually not as deep and long as in winter, because of higher ambient temperatures, but also due to seasonal functional plasticity. Unlike many other species, subtropical nectarivorous blossom-bats and desert spiny mice use more frequent and pronounced torpor in summer than in winter, which is related to seasonal availability of nectar or water. Thus, seasonal use of torpor is complex and differs among species and habitats.